2001
DOI: 10.1007/s100670170020
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Interleukin-2 Receptor in Sjo¨gren’s Syndrome: Relation to Main Serum Immunological and Immunohistochemical Parameters

Abstract: Our aim was to study sIL-2R relationship with main serum immunological and LSG immunohistochemical parameters, including surface antigen expression of immune activation, in 27 patients with primary SS. Serum sIL-2R levels were significantly higher in SS (p<0.00005), as well as in SLE (p<0.05) and RA (p< 0.000001) patients than in controls. In SS patients with abnormal slL-2R values (n = 7) we found higher levels of anti-SSB/La antibodies (p<0.05), IgM-RF (p<0.014) and CRP (p<0.003) with respect to those with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Serum IgG, soluble IL-2 receptor, ß 2 -microglobulin, anti-Ro/SSA, and anti-La/SSB have been found at elevated concentrations in sera from patients with SS, but none individually was sufficiently sensitive or specific to use for evaluation of disease activity 20,21,22 . Serum IgG, soluble IL-2 receptor, ß 2 -microglobulin, anti-Ro/SSA, and anti-La/SSB have been found at elevated concentrations in sera from patients with SS, but none individually was sufficiently sensitive or specific to use for evaluation of disease activity 20,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum IgG, soluble IL-2 receptor, ß 2 -microglobulin, anti-Ro/SSA, and anti-La/SSB have been found at elevated concentrations in sera from patients with SS, but none individually was sufficiently sensitive or specific to use for evaluation of disease activity 20,21,22 . Serum IgG, soluble IL-2 receptor, ß 2 -microglobulin, anti-Ro/SSA, and anti-La/SSB have been found at elevated concentrations in sera from patients with SS, but none individually was sufficiently sensitive or specific to use for evaluation of disease activity 20,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of this peptide have been estimated in many disease entities including malignancies, diseases of autoaggression and inflammation/infectious-based processes, where sIL-2R serum concentration frequently correlated with disease severity (De Rie et al 1996, Itoh et al 1998, Kami et al 2000, Kapp et al 1988, Matsumoto et al 1998, Nakata et al 1998, Niitsu et al 2001, Spadaro et al 2001, Suenaga et al 1998, Tartour et al 2001, Vonderheid et al 1998). Monitoring of sIL-2R serum levels is a useful method for the assessment of disease intensity, efficacy of provided treatment, and for prediction of further illness course.…”
Section: Introductionmentioning
confidence: 99%
“…In both diseases it has been reported that the expression level of HLA-DR in the epithelia is high 20,21 and that the proportion of CD4 ϩ Thelper cells in infiltrating cells is high, 22,23 suggesting the existence of a common immunological abnormality. Van De Merwe and colleagues proposed the following onset mechanism: autoantibodies blocking muscarinic receptors, which are involved in contraction of smooth muscles, are produced in patients with Sjögren's syndrome, thus resulting in interstitial cystitis.…”
Section: Discussionmentioning
confidence: 97%